Paris in the present tense [large type] - Helprin, Mark (Thorndike Press, 2018)
Jules is confronted headlong and all at once by a series of challenges to his principles, livelihood, and home, forcing him to grapple with his complex past and find a way forward. He risks fraud to save his terminally ill infant grandson, matches wits with a renegade insurance investigator, is drawn into an act of savage violence, and falls deeply, excitingly in love with a young cellist a third his age. He forges a denouement that is staggering in its humanity, elegance, and truth.